Pengaruh Intellectual Capital, Pembiayaan Musyarakah, dan Pembiayaan Murabahah Terhadap Kinerja Keuangan - Reyhan Kennardi Dewanto; Adam Sugiarto (eCo-Fin, 2023)
ABSTRACT This study was conducted to determine the effect of intellectual capital, musharakah financing, murabahah financing on financial performance in Islamic banks registered with the Financial Services Authority (OJK) for the 2017-2021 period The population in this study amounted to 14 banks. The sample was selected using the puposive sampling method and using the multiple linear regression method data analysis technique and the data will be processed using the Eviews application version 9, so that 6 banks with 14 total observations were obtained. The results of the hypothesis research state that intellectual capital, musharakah financing, and murabahah financing affect financial performance both partially and simultaneously in Islamic banks registered with the Financial Services Authority for the 2017-2021 period. Keywords: Intellectual Capital, Musyarakah Financing, Murabahah Financing, Financial Performance